The Effect Of Different Percentages Of Durian Seed Flour (Durio Zibethinus L) On The Physical Properties Of Edible Straw - salma siti fatimah; Ana Nadiya Afinatul Fishi; Sakina Yeti Kiptiyah (UNIVED Press, Dehasen University Bengkulu, 2026)
Purpose: This study aims to determine the effect of adding durian seed flour (Durio zibethinus L) on the physical properties of edible straw. Methodology: This study used an experimental method by producing durian seed flour and edible straw, then conducting several physical tests to determine the characteristics of the edible straw product. The design used in this study was a completely randomized design (CRD) using three levels of durian seed flour percentage (50%, 60%, 70%). Data analysis was performed using SPSS with ANOVA (Analysis of Variance) at a significance level of <0.05. If there was a significant effect, it was followed by Duncan's test. Results: The study showed that an increase in the percentage of durian seed flour significantly reduced the swelling ratio, indicating an increase in resistance to water absorption. The lowest swelling ratio values were obtained in the 60% and 70% treatments. In the temperature resistance test, all treatments were stable at 5°C and 25°C, while at 45°C, the 60% and 70% treatments showed better stability than the 50% treatment. The parameters of color, solubility, thickness, and texture showed no significant differences between treatments. Findings: Differences in durian seed flour percentage had a significant effect on several physical characteristics of edible straw. Novelty: This study utilized durian seeds as flour as the main ingredient in the production of edible straw. Originality: This study utilizes durian seed waste as an alternative to plastic straws. Conclusion: The addition of durian seed flour affects the swelling test results and resistance at 45°C. Type of Paper: research article.